2003
DOI: 10.1016/s0025-5408(03)00069-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen ionic conduction in brownmillerite CaAl0.5Fe0.5O2.5+

Abstract: The oxygen permeability of CaAl 0.5 Fe 0.5 O 2.5þd brownmillerite membranes at 1123-1273 K was found to be limited by the bulk ionic conduction, with an activation energy of 170 kJ/mol. The ion transference numbers in air are in the range 2 Â 10 À3 to 5 Â 10 À3 . The analysis of structural parameters showed that the ionic transport in the CaAl 0.5 Fe 0.5 O 2.5þd lattice is essentially along the c axis. The largest ion-migration channels are found in the perovskite-type layers formed by iron-oxygen octahedra, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…The oxygen ionic conductivity under oxidising conditions was estimated from the data on total conductivity and oxygen permeability, as described elsewhere. 6,[17][18][19] All data on oxygen permeation presented in this work correspond to the membrane feed-side oxygen partial pressure (p 2 ) fixed at 0.21 atm (atmospheric air).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxygen ionic conductivity under oxidising conditions was estimated from the data on total conductivity and oxygen permeability, as described elsewhere. 6,[17][18][19] All data on oxygen permeation presented in this work correspond to the membrane feed-side oxygen partial pressure (p 2 ) fixed at 0.21 atm (atmospheric air).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, XRD analysis of samples quenched from 800-950 • C showed no essential changes in the phase composition, in agreement with data on CaFe 0.5 Al 0.5 O 2.5+δ . 17 Such a behaviour might be advantageous for membrane applications, although further studies are necessary in order to reveal contributions of the constituent phases to total expansion of the ceramic materials.…”
Section: Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this type of improvement should mostly enhance the ionic conductivity, as the electronic conductivity is usually less sensitive to such microstructural features. In fact, the presence of ionblocking grain boundaries usually provides underestimated ionic transport numbers (14).…”
Section: Resultsmentioning
confidence: 99%
“…Oxide ion conduction in the Brownmillerite structure type has been studied since 1990, when Goodenough et al [28] reported an order-disorder transformation in Ba 2 In 2 O 5 leading to fast ion conduction above ∼925 • C. Ba 2 In 2 O 5 and its analogs have since been the subject of many studies linking the structures to the temperature dependence of the conductivity and behavior in the presence of water, CO 2 , and under reducing conditions. (see for example [29][30][31][32][33]) Figure 8 shows the in-situ XRD data for Ba 2 In 2 O 5 up to 1105 • C, in which the orthorhombic to tetragonal to cubic phase transformations are obvious. Although the XRD method is insensitive to the oxygen sublattice, the in-situ XRD measurements show the phase transformations clearly, and unambiguously provide the time dependence of the phase transformations.…”
Section: Applications In Electroceramicsmentioning
confidence: 99%